PENGARUH MEDIA PEMBELAJARAN PERMAINAN MONOPOLI TERHADAP KETERAMPILAN BERBICARA SISWA SMA N 5 KABUPATEN KEPULAUAN TANIMBAR - Naxa Elsina Luarmasse; Juliaans E R Marantika; Henderika Serpara (Universitas Pattimura, 2021)
The influence of the “monopoly game” as learning media on the speaking ability of students of the SMA N 5 Tanimbar Islands District (KKT). The aim of this research is to describe whether there is an influence of the